Crystal structure of azido-(N,N-dimethylbenzylamine-C2[1,3- bis(diphenylphosphino)propane-P,P′)]palladium(II), {Pd(C6H4CH2NMe2-C2)(N3)[(C6H5)2P(CH2)3P(C6H5)2-P,P′]} - de Almeida, E. T. [UNESP]; Santana, A. M. [UNESP]; de Godoy Netto, A. V. [UNESP]; Mauro, A. E. [UNESP]; Santos, M. P.; Santos, R. H.A. (De Gruyter, 2002)
C36H38N4P2Pd, monoclinic, P121/c1 (No. 14), a = 9.7373(4) Å, b = 15.909(1) Å, c = 21.690(1) Å, β = 94.650(4)°, V= 3349.0 Å3, Z = 4, Rgt(F) = 0.033, wRref(F2) = 0.122, T= 293 K. © 2014 Oldenbourg Wissenschaftsverlag GmbH, Rosenheimer Str. 145, 81671 München. All rights reserved.